THE INFLUENCE OF FINANCIAL TECHNOLOGY AND E-COMMERCE ON MSME INCOME IN SUMENEP - Arie Setyo Dwi Purnomo; Avinda Dwi Purnamasari (Jurnal Ekonomi, 2023)
This study aims to determine how MSMEs' incomes are affected by e-commerce and financial technology in the tourist area of Slopeng Beach, Sumenep Regency. A quantitative method was used in this studi. Participants on this study is members of the MSME business community who live near Sumenep's Slopeng Beach tourism. With a total of fifty respondents, the technique of purposeful sampling was used for the sampling. Multiple linear regression analysis was used for the data analysis. The study demonstrates that financial technology has not effect on MSME income. Nevertheless, income increases as a result of e-commerce. Sumenep's SME sector. E-commerce and financial technology, on the other hand, simultaneously raise SMEs' incomes in Sumenep.